Strategi Pendidikan Nilai dan Karakter - Karima Karima; Gusmaneli Gusmaneli (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research aims to describe in depth the approaches and strategies for values ​​and character education. This research uses a type of qualitative research that is a literature study. The data sources used in this research are books and scientific articles. The results of the research are that in implementing values ​​and character education it is necessary to have several value approaches, namely: spiritual values/tawheed, values ​​of love of knowledge, values ​​of integrity, values ​​of respect/respect for oneself and others, values ​​of responsibility, values ​​of hard work, values ​​of Istiqomah , the value of patience, the value of example, the value of tolerance and the value of friendship and the habituation strategy approach; exemplary strategy; and strengthening strategies